COMPARISON OF OXIDATIVE STRESS LEVELS DURING THE THIRD TRIMESTER IN NORMAL PREGNANCY AND PREECLAMPSIA - Taseer, Muneeza; Naima Shakeel,; Munira Taseer,; Fawad,; Faiza Rehman,; Durrira, (Journal of Ayub Medical College Abbottabad, 2023)
Background: The placenta is a complex transiently formed organ which plays a crucial role in the development of the foetus. As the placenta is responsible for maintaining pregnancy placental defects are mainly responsible for pregnancy-related issues. Preeclampsia is a pregnancy-related disorder due to uteroplacental insufficiency resulting from deficient remodelling of spiral arteries causing ischemic reperfusion injury which is finally responsible for the generation of reactive oxygen species and oxidative stress by the placenta. So, this study was planned to determine and compare serum levels of oxidative stress markers (ischemia-modified albumin and malondialdehyde) in preeclampsia and normal pregnancy in the third trimester. Methods: Study design: Cross-sectional comparative study Settings Gynae/Obs Department and Pathology Laboratory, Lahore General Hospital, Lahore. Study population: 42 Pregnant females at 34-36 weeks of gestation were selected. Group 1 compromised 21 normal healthy pregnant females and group 2 included 21 preeclamptic patients. Sampling technique: non-probability purposive sampling. Blood samples were taken at 34-36 weeks of gestation. Serum was stored for ischemia-modified albumin and malondialdehyde. Data was analyzed using SPSS version 20. An Independent t-test was used to compare values between the groups during the third trimester. A p-value of ‰¤0.05 was considered significant. Results: Comparison of ischemia-modified albumin and malondialdehyde values between group I and group 2 showed a highly significant difference of p-value of <0.001. Conclusion: Oxidative stress markers were higher in preeclamptic patients as compared to normal pregnant females during the third trimester suggesting the role of the placenta in oxidative stress.